PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PENINGKATAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Sholihah, Rohmah Jimi (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This study aims to describe the use of Artificial Intelligence (AI) in improving Islamic Religious Education learning. This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart spiral model approach, which involves the cycle of planning, implementing actions, observing, and reflecting. The results of the study showed that there was a significant increase in understanding of Islamic Religious Education material, there was an increase in student activeness in discussions, asking questions, and being involved in learning activities, which created a more dynamic learning atmosphere, there was a significant increase in practical skills in practical skills.